FAKTOR - FAKTOR YANG MEMPENGARUHI KINERJA KARYAWAN PADA PT. INDOMARCO PRISMATAMA MAKASSAR - Arfiany Arfiany (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2017)
The purpose of this study was How does the leadership, discipline, social security, job performance, work environment on employee performance. This study uses a quantitative method with a validity test was used to test the validity of the research data, the results obtained in the leadership variable (X1), discipline (X2), Social Security (X3), performance (X4) and workplace (X5) and the dependent variable (Y) obtained the numbers r count> r table. In hypothesis testing using t test (test the effect of partially / individual) obtained t leadership variable (X1), discipline (X2), Social Security (X3), performance (X4) and workplace (X5) partially and simultaneously there is a significant and positive effect on employee performance (Y).